Atmosphere, mood, and scientific explanation - Kirsh, David (Frontiers in Computer Science, 2023)
In this paper I consider how scientific theories may explain architectural atmosphere. Architects use atmosphere to refer to a holistic, emergent property of a space that partly determines the mood of inhabitants. It is said to be a "subtle, intangible, ambient quality of a place" that also significantly shapes the way we interact with a space. It is caused by the way light, texture, materials, layout, geometry, acoustics, smell, and other perceptual properties influence affect. But it goes beyond these individually because of non-linear interactions between them. In sections one and two, I explain what an externalist account of atmosphere would look like. This is an interpretation that objectifies atmosphere, treating it as a complex causal property of buildings and spaces, accessible to scientific study through ethnographic research, through quantifying and minutely observing and recording humans and the buildings they are in, and then using machine learning and statistical analyses to identify correlations. The goal is to push the identification of the underlying external attributes as far as possible, ultimately to where a machine might enter a room, move around and then label its atmosphere. In section three, I explore an internalist or subjectivist account of atmosphere. This is the position that pushes back on machine identification of atmospheres. A subjectivist interpretation is harder to study scientifically because it involves knowing so much about the inner state and the history of a person. Culture, incoming mood, prior experience and associations, interests, tasks, social interaction and more may all affect mood. Section four explores the frequently underestimated roleon emotion and space comprehension played by the tasks that occupants perform while in a space, and the way their surrounding social and technological context intrudes on their encounter. I introduce and defend the view that tasks, social context, and nearby technology situate a person in a different environment than when they are inactive. This complicates the search for atmosphere. Nonetheless, I end on an optimistic note that there may yet be a place for atmosphere in a neuroscience of architecture, but it will be much different than our current thinking.